The Employee Green Behavior and Green HR Practice, The Role of Transformational Green Leadership : A Review Literature - Eka Risma Putri; Fauziah Maharani (Adpebi Science Series, 2024)
Environmental sustainability is the responsibility of all parties. The company as an element that contributes greatly to environmental damage must be brave enough to face the demands of the world community to pay attention to environmental sustainability. Environmentally friendly behavior is one of the imperatives for organizations to realize environmental sustainability. Therefore, it is important to understand the organizational elements and practices that influence environmentally friendly actions. The purpose of this paper is to review the environmentally friendly behavior of employees, green HR practices that support the creation of environmentally friendly behavior of employees and the role of green transformational leadership that directs and becomes a model for the achievement of corporate environmental performance